This is how I lied - Gudenkauf, Heather (Park Row Books, 2020)
"Det. Maggie Kennedy-O'Keefe of the Grotto, Iowa, PD is assigned to a cold case, the murder of her 16-year-old best friend, Eve Knox, after two kids find a new piece of evidence, Eve's boot, in the cave where Maggie found Eve's body 25 years earlier."--